Does Intellectual Capital Matter for Organizational Performance? (a Case Study) - Aslam Mei Nur Widigdo; Sepky Mardian (Dinasti Publisher, 2024)
Organizational performance is one of the determining factors for sustainability. SD MM as one of the Islamic Mass Organization charities located in Limo Depok has performed less than optimally in the last 5 years. This study aims to determine and analyze the influence of intellectual capital, which consists of human capital, structural capital, and relational capital, on the organizational performance of the SD MM. The method used in this study is a research approach with a quantitative paradigm, using closed questionnaire research instruments, causality analysis with SEM (Structural Equation Modeling), and the use of SPLS (Part Least Square) as a statistical analysis tool. The respondents were all teachers and staff from SD MM as amount of 44. Sampling using saturated sampling techniques. The results showed that Human Capital does not affect organizational performance. Meanwhile, Relational Capital and Structural Capital partially have a significant positive effect on the organizational performance of SD MM.